The role of calcium-fortified milk in preventing osteoporosis in the elderly: A Literature Review - Lukman Waris (DAPU Aceh Publishing, 2025)
Osteoporosis is a common degenerative disease among the elderly that increases fracture risk and ranks among the top 10 global degenerative conditions according to WHO. This study reviews evidence on the effectiveness of calcium-rich milk and dairy products in preventing osteoporosis in older adults. This is a review was conducted using purposive sampling of journal articles from 2008 to 2022 from Google Scholar. Studies were evaluated based on Elwood’s framework, focusing on evidence description, internal and external validity, and biological plausibility. As a result, all articles confirmed calcium’s role in bone formation and maintenance. Two review articles highlighted the importance of calcium and vitamin D for bone health, particularly in specific groups like long-term corticosteroid users and older adults with mineral imbalances; however, they lacked empirical data and statistical analysis. Two cross-sectional studies showed associations between calcium intake and improved bone mineral density or reduced osteoporosis risk, but limitations such as uncontrolled confounders and incomplete statistics reduce confidence in these findings. No longitudinal or randomized controlled trials were identified to establish causality or dose-response relationships. Although calcium is essential for bone health, current evidence is insufficient to conclusively support calcium-fortified milk as an effective intervention to prevent osteoporosis in the elderly. Further longitudinal and randomized controlled studies are necessary to provide robust data to inform public health policies. As an immediate step, health practitioners should promote a balanced diet rich in calcium and vitamin D alongside lifestyle modifications such as regular weight-bearing exercise to support bone health in older adults.